2016
DOI: 10.1177/1556264616668973
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Biomedical Research Trust Scale (BRTS) in English and Spanish

Abstract: This study developed and validated the Biomedical Research Trust Scale (BRTS), a 10-item measure of global trust in biomedical research, in English and Spanish (BRTS-SP). In total, 85 English- and 85 Spanish-speaking participants completed the BRTS or BRTS-SP, as well as measures of biobanking attitudes, self-efficacy, receptivity, and intentions to donate blood or urine. Results indicated the BRTS and BRTS-SP showed adequate internal consistency in both English and Spanish. In addition, greater levels of trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our results are comparable with those of previous studies examining the effectiveness of LGBT competency training interventions developed for specific disciplines, such as emergency medicine and geriatric care. [30][31][32][33][34][35][36][37][38] In addition to effectiveness and acceptability of content, similar to other online training programs for oncology nurses, the COLORS training was well received and was conducive to learning among oncologists. 37 However, the COLORS training was also unique in several aspects, as mentioned above.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our results are comparable with those of previous studies examining the effectiveness of LGBT competency training interventions developed for specific disciplines, such as emergency medicine and geriatric care. [30][31][32][33][34][35][36][37][38] In addition to effectiveness and acceptability of content, similar to other online training programs for oncology nurses, the COLORS training was well received and was conducive to learning among oncologists. 37 However, the COLORS training was also unique in several aspects, as mentioned above.…”
Section: Discussionmentioning
confidence: 87%
“…Most existing trainings cover general topics relevant to the care of LGBT patients, such as sexual orientation and gender‐related terminology, inclusive language and communication, and health disparities commonly experienced within the LGBT community . Additionally, there are specific trainings that have been developed and examined for medical students, nurses, emergency room care providers, and providers caring for geriatric patients . These studies showed that training improved LGBT‐related knowledge and attitudes among health care providers, but few have examined changes in clinical practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the past studies, several factors influence an individual's level of trust in research including socioeconomic status, cultural beliefs, and personal or interpersonal experiences with research and health care providers [2,[8][9][10]. However, measuring this concept in biomedical research is likely different from measuring trust in healthcare and other areas, especially among those underrepresented in research [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a major disadvantage of these measuresespecially those used in healthcare settingsis the neglect of domains that might be particularly important to people less likely to voluntarily participate in medical researche.g., safety, fairness, communication, and honesty. This creates a critical gap in our understanding of trust across populations [11].…”
Section: Introductionmentioning
confidence: 99%